International Noise Awareness Day – INAD Brazil 2024 - Fonseca, William D'Andrea; Kuniyoshi, Isabel Cristiane (Acústica e Vibrações, 2024)
This paper presents Brazil’s 2024 INAD campaign, whose slogan is “Noise at work? Prevention is the solution!”. After contextualizing the International Noise Awareness Day and its development in Brazil, the text discusses the focus on occupational health and the campaign’s main awareness goals. It examines the national regulatory framework, the direct and indirect effects of noise exposure, additional accident risks, and the synergistic impact of ototoxic agents. The paper outlines preventive guidelines grounded in engineering controls, exposure management, and safety culture, and highlights the role of educational materials and outreach activities. Emphasis is placed on the articulation between acoustic engineering, occupational health, and education as the basis for consolidating a culture of prevention and reducing the impact of noise in workplaces across different productive sectors. The article also points to opportunities for technical and social engagement of the acoustics community.